Novel magnetic composites based on water soluble unsaturated polyester resin and iron oxide nanoparticles - Petar Velev; Rayna Bryaskova (Fracture and Structural Integrity)
Magnetic nanocomposites on the basis of water soluble unsaturated polyester resin filled with different amount of iron oxide nanoparticles have been successfully prepared. The mechanical properties of thus prepared composites as tensile, impact and flexural strength were determined. The specific volume and surface resistance of the magnetic nanocomposites were also determined.